Therapeutic strategies for severe COVID-19: a position paper from the Italian Society of Infectious and Tropical Diseases (SIMIT) - Mussini, Cristina; Falcone, Marco; Nozza, Silvia; Sagnelli, Caterina; Parrella, Roberto; Meschiari, Marianna; Petrosillo, Nicola; Mastroianni, Claudio; Cascio, Antonio; Iaria, Chiara; Galli, Massimo; Chirianni, Antonio; et al. (Clinical microbiology and infection, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has become pandemic, reaching almost one million death worldwide. At present standard treatment for coronavirus disease 2019 (COVID-19) is not well defined because the evidence, either from randomized or observational studies, with conflicting results, has led to rapid changes in treatment guidelines. Our aim was to narratively summarize the available literature on the management of COVID-19 in order to combine current evidence and interpretation of the data by experts who are treating patients in the frontline setting. The panel conducted a detailed review of the literature and eventual press releases from randomized clinical trials for each possible available treatment. Inductive PubMed search waws performed for publications relevant to the topic, including all clinical trials conducted. The result was a flowchart with treatment indications for patients with COVID-19. After 6 months of a pandemic situation and before a possible second coronavirus wave descends on Europe, it is important to evaluate which drugs proved to be effective while also considering that results from many randomized clinical trials are still awaited. Indeed, among treatments for COVID-19, only glucocorticoids have resulted in an association with a significant decrease in mortality in published randomized controlled trials. New therapeutic strategies are urgently needed.